Ursodeoxycholic and deoxycholic acids: A good and a bad bile acid for intestinal calcium absorption - Rodriguez, Valeria Andrea (2013)
The aim of this study was to investigate the effect of ursodeoxycholic acid (UDCA) on intestinal Ca2+ absorption and to find out whether the inhibition of this process caused by NaDOC could be prevented by UDCA. Chicks were employed and divided into four groups: (a) controls, (b) treated with 10 mM NaDOC, (c) treated with 60 lg UDCA/100 g of b.w., and (d) treated with 10 mM NaDOC and 60 lg UDCA/100 g of b.w. UDCA enhanced intestinal Ca2+ absorption, which was time and dose-dependent. UDCA avoided the inhibition of intestinal Ca2+ absorption caused by NaDOC. Both bile acids altered protein and gene expression of molecules involved in the transcellular pathway of intestinal Ca2+ absorption, but in the opposite way. UDCA aborted the oxidative stress produced by NaDOC in the intestine. UDCA and UDCA plus NaDOC increased vitamin D receptor protein expression. In conclusion, UDCA is a bene- ficial bile acid for intestinal Ca2+ absorption. Contrarily, NaDOC inhibits the intestinal cation absorption through triggering oxidative stress. The use of UDCA in patients with cholestasis would be benefited because of the protective effect on the intestinal Ca2+ absorption, avoiding the inhibition caused by hydrophobic bile acids and neutralizing the oxidative stress.